Influence of heat treatment on tribocorrosion properties of Ni-B composite coatings - Khoma, M.; Mardarevych, R.; Vynar, V.; Vasyliv, Сh.; Kovalchyk, Yu. (Problems of Tribology, 2022)
Various surface protection technologies, in particular, electrochemical, are used to increase the wear and corrosion resistance of steels and alloys. Composite electrochemical coatings (CEC) technology is more promising than "pure" galvanic coatings. Application of CEC increases the wear, corrosion and fatigue failure resistance of metals. Nickel often is chosen as a CEC matrix because it easily forms uniformly filled defect-free composite structures with many particles of the dispersed phase (DP). Physical and mechanical properties of metal coatings determine practical application of such composition. The characteristics of nickel-based CEC are: high hardness and strength, significant corrosion resistance in atmospheric environment, as well as in alkali and mild acidy environments. An effective composition coating with tribological designation can be CEC Ni-B, received in the process of electrolysis from suspension of amorphous boron in nickel electrolyte. A new composite structure of matrix filled type Ni-Ni3B is formed after heat treatment. Composition and structure of coating is determined by regimes of diffusion annealing. Ni-B coatings increase wear resistance of steel in chlorine-based environments. The influence of low-temperature thermal treatment of Ni-B CEC on steel 09Mn2Si on their tribocorrosion behavior is investigated. It is shown that the structural factor has a decisive influence on the efficiency of such friction pairs. The CEC has the least wear and the most positive compromise electrode potential after vacuum annealing at 450°C, when the initial stage of solid-phase interaction of coating components with the formation of Ni-Ni3B occurs.